Professional and Organized Criminals: Similarities and Differences - Nikolić, Zlatko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2009)
There isn’t a day that goes by that we don’t hear about newly discovered organised criminal groups, special court and prosecutor procedures and police actions through printed or electronic media. The public is literally swamped by press releases about "mafia" groups of all kinds, almost as if nothing else happens in the area of crime and criminality. What is "mafia" or organised crime really, and which visible characteristics does it have? Is there any other type of criminality, or is all crime organised and "mafia" type?